GRIN2B mutations in west syndrome and intellectual disability with focal epilepsy. Issue 1 (2nd January 2014) - Lemke, Johannes R.; Hendrickx, Rik; Geider, Kirsten; Laube, Bodo; Schwake, Michael; Harvey, Robert J.; James, Victoria M.; Pepler, Alex; Steiner, Isabelle; Hörtnagel, Konstanze; Neidhardt, John; Ruf, Susanne; et al.
<x xml:space="preserve">Abstract</x> Objective To identify novel epilepsy genes using a panel approach and describe the functional consequences of mutations. Methods Using a panel approach, we screened 357 patients comprising a vast spectrum of epileptic disorders for defects in genes known to contribute to epilepsy and/or intellectual disability (ID). After detection of mutations in a novel epilepsy gene, we investigated functional effects in Xenopus laevis oocytes and screened a follow‐up cohort. Results We revealed de novo mutations in GRIN2B encoding the NR2B subunit of the N‐methyl‐D‐aspartate (NMDA) receptor in 2 individuals with West syndrome and severe developmental delay as well as 1 individual with ID and focal epilepsy. The patient with ID and focal epilepsy had a missense mutation in the extracellular glutamate‐binding domain (p.Arg540His), whereas both West syndrome patients carried missense mutations within the NR2B ion channel‐forming re‐entrant loop (p.Asn615Ile, p.Val618Gly). Subsequent screening of 47 patients with unexplained infantile spasms did not reveal additional de novo mutations, but detected a carrier of a novel inherited GRIN2B splice site variant in close proximity (c.2011‐5_2011‐4delTC). Mutations p.Asn615Ile and p.Val618Gly cause a significantly reduced Mg2+ block and higher Ca2+ permeability, leading to a dramatically increased Ca2+ influx, whereas p.Arg540His caused less severe disturbance of channel function, corresponding to the milder patient phenotype. Interpretation We identified GRIN2B gain‐of‐function mutations as a cause of West syndrome with severe developmental delay as well as of ID with childhood onset focal epilepsy. Severely disturbed channel function corresponded to severe clinical phenotypes, underlining the important role of facilitated NMDA receptor signaling in epileptogenesis. ANN NEUROL 2014;75:147–154